The Role of Whole-Body MRI in Patients with Lymphoma: A Narrative Review - Benedetta Renzetti MD; Arrigo Cattabriga MD; Stefano Brocchi MD; Caterina Gaudiano MD; Marta Assenza; Cristina Nanni MD; Alessandro Broccoli PhD, MD; Antonio Basile MD; PierLuigi Zinzani PhD, MD; Stefano Fanti MD; Cristina Mosconi MD (Technology in Cancer Research & Treatment)
Lymphomas, including Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL), represent a significant proportion of malignancies affecting diverse age groups, including children and pregnant women. Traditional imaging modalities, such as 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) and contrast-enhanced CT, are standard for staging and monitoring but expose patients to ionizing radiation, increasing the risk of secondary malignancies. This review evaluates whole-body magnetic resonance imaging (WB-MRI) as a radiation-free alternative for assessing lymphoproliferative disorders. We examine its strengths, including the ability to detect disease and assess treatment response, as well as its limitations, such as challenges in visualizing small thoracic lesions. Recent studies demonstrate high concordance between WB-MRI and 18F-FDG-PET/CT, particularly for lymphomas with low or variable FDG avidity, making WB-MRI a promising modality for staging and follow-up, especially in young and pregnant patients.